Unravelling hidden inequities in a universal public long-term care system - Vidiella-Martin, J; Hernández-Pizarro, HM; García-Gómez, P; López-Casasnovas, G (Elsevier, 2024)
We study the socioeconomic horizontal inequity in the allocation of publicly subsidised long-term care (LTC) in Spain, using administrative data from the universe of applicants in Catalonia. We find that, after controlling for needs, cash subsidies for informal care are disproportionately concentrated among wealthier individuals, while the use of formal care services (home care and nursing homes) is concentrated among the less well-off. This suggests that cash benefits may inadvertently facilitate access to wealthier individuals’ private care. We also find inequity in the form of provision, with in-kind services being more prevalent among the worse-off while wealthier beneficiaries are more likely to receive vouchers. While this duality in provision does not lead to significant differences in overall time to access LTC, we find that lower-income individuals wait longer for telecare, and wealthier individuals opting for in-kind nursing home care wait longer, suggesting potential differences in preferences or constraints. We find no evidence of socioeconomic inequity in the time spent navigating the administrative application process. Our findings highlight the need for policymakers to consider the potential unintended consequences of cash benefits and different forms of provision to ensure equitable access to LTC services.